Proposed Model for Inter-Institutional Collaboration on Instructional Design Projects - Blick, Andrew; Waters, Todd (The Northwest eLearning Journal, 2021)
Instructional design requests are multi-faceted and complex, necessitating a broad skill set and efficacious problem-solving procedures. While individual instructional designers in higher education are effective in their work, partnering with designers from other higher education institutions allows them to leverage one another’s experiences, skills, and approaches to these complex design requests. There is much research regarding instructional design processes, but there is none that addresses inter-institutional collaborative efforts to address complicated instructional design requests from faculty and subject-matter experts. In this article, we review current trends and discussions of instructional design models and practices and applicable communication theories and practices. We then propose a model for cross-institutional collaboration based on instructional design, communication, and collaborative processes.